Kompetencje a zachowania edukacyjne dorosłych Polaków - Grześkowiak, Alicja (Annales. Etyka w Życiu Gospodarczym, 2016)
Increasing activity in the field of lifelong learning is an important educational goal of the European Union. The rapidly changing environment creating new demands makes it necessary to take action in the field of continuous education. Labour market requirements in the process of evolving towards a knowledge-based society are changing, which is particularly important in the era of population ageing and raising the retirement age. All forms of education: formal, non-formal and informal should gain importance in response to the growing requirements. The situation in Poland is vary unfavourable when comparing the participation in activities related to lifelong learning with other European Union countries. Research indicates various demographic, social and economic determinants of adult engagement in lifelong learning. This study attempts to assess the relationships between the level of competences in various areas and the educational behaviours of adult Poles. The analyses are based on individual data from a national survey on human capital. The crucial purpose, which is to identify interdependences among the considered factors, attitudes and behaviours, is accomplished by selected statistical and econometric methods supported by suitable data visualization techniques.